A Low Cost 4 DOF Remotely Operated Underwater Vehicle Integrated With IMU and Pressure Sensor - Mohd Aras, Mohd Shahrieel; Ab Azis, Fadilah; Othman, Muhammad Nur (2012)
This paper presents the development of low cost Remotely Operated Underwater Vehicle (ROV) for underwater activities. In underwater industries, the constraint issues to the divers are the dangerous environment and depth pressurized that affect human bodies. Otherwise high cost is needed for each underwater task. Many industries are involved on robot development in order to reduce human works as well as increase productivity, efficiency and monitoring. Therefore, ROV is designed in order to replace the divers itself. The micro ROV was design based in three goals maneuverability, performance and future industrial implementation (ability to carry payload) with minimum cost. The Peripheral Interface Controller (PIC) is used to control the movement of this ROV. Standard test method for pressure testing, buoyancy and controlling efficiencies are considered on testing the ROV. In this project the focus will be in controlling an ROV in a multiaxis motion in order to maintain its desired position. The verified algorithms will then be tested on the actual prototype micro ROV. This project will give much benefit for related underwater industries by looking at ROV's features with needed minimum cost of implementation.